All in This Together? A Preregistered Report on Deservingness of Government Aid During the COVID-19 Pandemic. Issue 3 (31st March 2022) - Bridgman, Aengus; Merkley, Eric; Loewen, Peter John; Owen, Taylor; Ruths, Derek
Abstract: The COVID-19 pandemic has placed unprecedented pressure on governments to engage in widespread cash transfers directly to citizens to help mitigate economic losses. Major and near-universal redistribution efforts have been deployed, but there is remarkably little understanding of where the mass public believes financial support is warranted. Using experimental evidence, we evaluate whether considerations related to deservingness, similarity, and prejudicial attitudes structure support for these transfers. A preregistered experiment found broad, generous, and nondiscriminatory support for direct cash transfers related to COVID-19 in Canada. The second study, accepted as a preregistered report, further probes these dynamics by comparing COVID-19-related outlays with nonemergency ones. We find that COVID-19-related spending was more universal as compared to a more generic cash allocation program. Given that the results were driven by the income of hypothetical recipients, we find broad support for disaster relief that is not means-tested or otherwise constrained by pre-disaster income.